Optimizing Urban Traffic Flow: A Case Study of Yavatmal City - Bharat R. Pawar; Aditya N. Pagrut; Ruchita H. Gautam; Kiran S. Bodade; Jitendra R. Sawant (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The research paper explores the critical issue of urban traffic congestion in Yavatmal, a rapidly developing mid-sized city in Maharashtra. It emphasizes how the city’s infrastructural growth has not kept pace with the increasing urbanization and rise in vehicular traffic, resulting in significant challenges for mobility and traffic management. The study adopts a multidisciplinary and empirical methodology, combining both qualitative and quantitative data such as field observations, traffic counts, stakeholder interviews, and secondary municipal data to gain a comprehensive understanding of the traffic dynamics in the city. Findings from the research reveal that the major contributors to congestion include insufficient road infrastructure, lack of traffic signal systems, disorganized public transport, unregulated parking, and poor adherence to traffic rules. These issues are exacerbated by the continued dependence on outdated and manual traffic control methods, which are unable to cope with the growing complexity of urban traffic. The paper critiques the limitations of existing traffic management practices and contrasts them with more advanced and technology-driven solutions implemented in comparable cities. These include adaptive traffic signals, real-time traffic monitoring, dedicated non-motorized lanes, and improved public transport integration. The analysis demonstrates that modern strategies are more efficient and responsive to dynamic traffic conditions